Middle Triassic (Anisian) Limestones from Bled, Northwestern Slovenia: Microfacies and Microfossils - Flügel, Erik; Ramovš, Anton; Bucur, Ioan I. (Geologija, 1993)
Microfacies types (predominantly intrabioclastic grainstones) and microfossils (predominantly dasycladacean algae and diverse foraminifera) characterize the Anisian carbonates near Bled (Castle Hill) and in the area westnorthwest of Bled as subtidal to intertidal shelf sediments deposited in the inner part of the Julian carbonate platform. The age of the carbonates is Middle Anisian (Pelsonian) according to the biozonation based on foraminifera and dasycladaceans.